El capital esclavista-mercantil en las Américas y su superación - del Nero da Costa, Iraci (2018)
In the article entitled América y el capital mercantil esclavista the authors exposed the elements underlying the slave-mercantile capital and indicated the limitations that were imposed to such capital. In the present article – after having being identified, in the hypothetical plan, the necessary conditions for overcoming the slave-mercantile capital – it presents the immediate historical causes of this overcoming for the vast majority of nations and other existing colonies in the Americas. It discusses also the relationship between the extinction of slavery, as part of a political character, and the suppression of the slave-mercantile capital, which is characterized by its eminently economic dimension.